FRI0280 Structural progression of ankylosing spondylitis associated with elevation in two novel, inflammatory biomarkers; matrix metalloproteinase and cathepsin-derived CRP. (23rd January 2014) - Bay-Jensen, A.C.; Karsdal, M.A.; Leeming, D.J.; Wichuk, S.; Maksymowych, W.P.; Qvist, P.
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic inflammatory disease, however current inflammatory biomarkers, such as CRP, have insufficient sensitivity and specificity to be broadly accepted in the diagnosis and prognosis of AS. We hypothesized, that quantification of inflammation markers derived from the affected tissue might have improved clinical utility compared to the systemic markers. We therefore developed two novel biomarker assays detecting MMP and Cathepsin-derived CRP. Both CRP-MMP and CRP-CAT has been reported to be elevated in AS compared to controls, whereas full-length CRP was not. Objectives: To determine cohort of patients with AS, the clinical utility of CRP-MMP and CRP-CAT including (1) diagnostic sensitivity & specificity, (2) association with long-term radiological changes in the spine (modified Stoke AS Spinal Score (mSASSS)). Methods: Serum samples (n=124) obtained from AS patients was available for this study. Mean duration of disease was 18, 0±11, 4 years (mean±SD). Within this cohort, samples from 16 AS patients with structural progression over two years and 29 without were selected for evaluation of the prognostic value of the marker set (sub-cohort 1A). Structural progression was achieved in subjects having a baseline mSASSS of at least 10 units increasing with at least 5 units over two years, and simultaneously the occurrence of at least one new syndesmophyte. Sub-cohort 1B contained samples from 53 AS patients from cohort 1, and these originated from patients who subsequently received anti-TNF treatment for three months and was then re-tested with the marker panel. Finally, we included serum samples (n=39) from healthy subjects as additional controls (Cohort 2). Serum samples were tested for CRP-MMP and CRP-CAT. Results: For baseline evaluations, data from cohort 1 and 2 were used. CRP-MMP and CRP-CAT were both elevated in AS compared to controls; 9.84±4.40 ng/ml (mean ± SD) vs 4.82±1.49 ng/ml (p<0.05), respectively, for CRP-MMP; and 299.6±137.6 ng/ml vs 178.6±54.03 ng/ml (p<0.05), for CRP-MMP. Diagnostic capability was assessed by ROC analysis, and AUC was 0.94 (p<0.0001) and 0.85 (p<0.0001) for CRP-MMP and CRP-CAT, respectively. In AS patients with structural progression over two years (sub-cohort 1A), CRP-MMP and CRP-CAT were significantly elevated at baseline compared to non-progressors, whereas hsCRP was not; 9.2±3.1 ng/ml vs 7.6±2.2 ng/ml for CRP-MMP, 276±108 ng/ml vs 218±67 ng/ml for CRP-CAT, and 21.9±25.6 ng/ml vs 12.7±21.5 ng/ml for hsCRP, respectively. Finally, both CRP-related markers decreased significantly after short term (2-3 months) of anti-TNF treatment (sub-cohort 1B). Conclusions: We have here confirmed the original observation that MMP and Cathepsin-derived fragments of CRP, both are significantly elevated in AS patients. Importantly, both markers, but not CRP, were significantly elevated at baseline in patients having structural progression defined by a composite index including mSASSS and syndesmophyte quantification. Further studies are needed to determine if the suggested association of the two CRP-fragments with structural deterioration of AS reflects a metabolic link to pathological processes in the spine. Disclosure of Interest: None Declared